An overview of the SOLVE/THESEO 2000 campaign - Newman, Paul A.; Harris, Neil R. P.; Adriani, Alberto; Amanatidis, Georgios T.; Anderson, James G.; Braathen, Geir O.; Brune, William H.; Carslaw, Kenneth S.; Craig, Michael S.; Decola, Philip L.; Guirlet, Marielle; Hipskind, R. Stephen; et al. (Journal of Geophysical Research, 2002)
International audience Between November 1999 and April 2000, two major field experiments, the Stratospheric Aerosol and Gas Experiment (SAGE) III Ozone Loss and Validation Experiment (SOLVE) and the Third European Stratospheric Experiment on Ozone (THESEO 2000), collaborated to form the largest field campaign yet mounted to study Arctic ozone loss. This international campaign involved more than 500 scientists from over 20 countries. These scientists made measurements across the high and middle latitudes of the Northern Hemisphere. The main scientific aims of SOLVE/THESEO 2000 were to study (1) the processes leading to ozone loss in the Arctic vortex and (2) the effect on ozone amounts over northern midlatitudes. The campaign included satellites, research balloons, six aircraft, ground stations, and scores of ozonesondes. Campaign activities were principally conducted in three intensive measurement phases centered on early December 1999, late January 2000, and early March 2000. Observations made during the campaign showed that temperatures were below normal in the polar lower stratosphere over the course of the 1999-2000 winter. Because of these low temperatures, extensive polar stratospheric clouds (PSC) formed across the Arctic. Large particles containing nitric acid trihydrate were observed for the first time, showing that denitrification can occur without the formation of ice particles. Heterogeneous chemical reactions on the surfaces of the PSC particles produced high levels of reactive chlorine within the polar vortex by early January. This reactive chlorine catalytically destroyed about 60% of the ozone in a layer near 20 km between late January and mid-March 2000, with good agreement being found between a number of empirical and modeling studies. The measurements made during SOLVE/THESEO 2000 have improved our understanding of key photochemical parameters and the evolution of ozone-destroying forms of chlorine.